Circuit film, electric circuit body, healthcare sensor, and wearable sensor

JP2025036337APending Publication Date: 2025-03-14TORAY INDUSTRIES INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024147462
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-31
Filing Date
2024-08-29
Publication Date
2025-03-14

AI Technical Summary

Benefits of technology

【0016】 本発明によれば、柔軟性と復元性が高く、かつ、形成した電気回路体を変形させた後の回路抵抗値が安定的である回路用フィルムを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036337000001_ABST
    Figure 2025036337000001_ABST
Patent Text Reader

Abstract

To provide a circuit film that exhibits high flexibility and resilience, ensuring stable circuit resistance after deformation of the formed electric circuit body.SOLUTION: The present invention provides a circuit film having a resilience of 20% or more and a stress relaxation rate of 0.9% / sec or less at 5 seconds after 50% strain.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a circuit film that is flexible, has high recovery and a fast stress relaxation rate, and to an electric circuit, a healthcare sensor, and a wearable sensor that use the same. [Background technology]

[0002] As the IoT (Internet of Things) society advances, sensors that detect minute changes in pressure, temperature, distortion, etc. are being attached to various objects in our daily lives, and utilizing this data is helping to improve our quality of life.

[0003] Furthermore, once devices that allow such sensors to be attached to the human body for long periods of time without feeling unnatural are put into practical use, it will become possible to easily obtain long-term data on the human body that, until now, could only be obtained for a short period of time even using special equipment. This is expected to dramatically change our lives, such as by enabling the prevention of diseases that were previously difficult to detect, and the improvement of skills in sports, music, and other areas.

[0004] Small devices equipped with sensors and other devices have been used in the past, and resin films have been used as the base material. However, films with rigid chemical bonds such as polyimide can be bent freely, but it is difficult to deform easily or quickly restore their original shape. Therefore, there is a demand for resin films that can be bent and stretched freely. In addition, these films are required to prevent the sensors and wiring from deteriorating under the conditions of use, just like existing film materials.

[0005] As an example of an existing resin film that can be freely bent and stretched, Patent Document 1 proposes "a polyurethane produced by reacting a polyether polyol (a) having a carbonate bond with an isocyanate compound (b), wherein the polyether polyol (a) has a hydroxyl value of 55 or less."

[0006] Furthermore, Patent Document 2 proposes "an active energy ray-curable resin composition comprising at least (a-1) a polyisocyanate, (a-2) a low molecular weight polyol having an alicyclic structure and a number average molecular weight of 500 or less, and (a-3) a urethane (meth)acrylate oligomer (A) which is a reaction product of a hydroxyalkyl (meth)acrylate, wherein the calculated network inter-crosslinking molecular weight of the composition is 1000 or more and 6000 or less."

[0007] Furthermore, Non-Patent Document 1 proposes a crosslinkable industrial silicone film.

[0008] Furthermore, as a material that has excellent elasticity and is easy to handle as a resin film, Patent Document 3 proposes "a flexible resin-forming composition containing (A) an elastomer containing monomer units derived from styrene, (B) a polymerizable compound, and (C) a polymerization initiator, in which the mass ratio of the monomer units derived from styrene to the total amount of (A) the elastomer is 27 mass% or more."

[0009] Furthermore, Patent Document 4 proposes a "curable resin composition for forming a flexible resin, comprising (A) a styrene-based elastomer, (B) a polymerizable monomer, and (C) a polymerization initiator, wherein the polymerizable monomer contains a silicone compound having a (meth)acryloyloxy group." [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2015-189886 A [Patent Document 2] JP 2010-222568 A [Patent Document 3] JP 2018-172460 A [Patent Document 4] JP 2018-203827 A [Non-patent literature]

[0011] [Non-Patent Document 1] Asahi Kasei Wacker Homepage "ELASTOSIL" (registered trademark) FILM2030 http: / / www.aws-silicone.com / dcms_media / other / EL%20FILM.pdf Summary of the Invention [Problem to be solved by the invention]

[0012] In devices such as the above-mentioned sensors, so-called wearable sensors and healthcare sensors, the circuit film is required to have flexibility and restorability to allow free bending and stretching when attached to the human body, etc., as well as a stable circuit resistance value after the formed electric circuit is deformed. However, the materials proposed in Patent Documents 1 to 4 do not all meet these requirements.

[0013] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a film for circuits which has high flexibility and recovery and which provides a stable circuit resistance value after the formed electric circuit is deformed. [Means for solving the problem]

[0014] In order to solve the above problems, the present inventors have conducted extensive research and have completed the following invention. That is, one preferred embodiment of the present invention is as follows.

[0015] <1> A film for circuits having a restoration rate of 20% or more, The stress relaxation rate at 5 seconds after 50% strain is 0.9% / sec or less. Film for circuits. How to measure resilience: With an initial chuck distance of 20 mm and a tensile speed of 300 mm / min, the test piece is stretched to a strain of 10 mm (50%), after which the tensile load on the test piece is released and the distance marked as the initial test length before the measurement is measured and regarded as L mm. The recovery rate is calculated from the following formula. Recovery rate [%] = (1-(L-20) / 10) x 100 Method for measuring stress relaxation rate at 5 seconds after 50% strain: With an initial chuck distance of 40 mm and a tensile speed of 300 mm / min, the test piece is stretched to a strain of 20 mm (50%) and held in that state for 10 minutes. The stress is measured every 1 second from the start of stretching while the strain is held at 50% for 10 minutes. The stress at x seconds after 50% strain is defined as σx and calculated using the following formula. (Stress relaxation rate at 5 seconds after 50% strain [% / sec]) = ((σ6-σ5) / σ0) × 100 Effect of the Invention

[0016] According to the present invention, it is possible to provide a film for circuits which has high flexibility and recovery and which provides a stable circuit resistance value after the formed electric circuit is deformed. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a film for circuits in the present invention. [Diagram 2] FIG. 1 is a cross-sectional view showing an example of a laminate using a circuit film according to the present invention. [Diagram 3] FIG. 1 is a cross-sectional view showing an example of a laminate using a circuit film according to the present invention. [Figure 4] FIG. 2 is a plan view showing an example of an electric circuit body according to the present invention. [Diagram 5] FIG. 2 is a plan view showing an example of an electric circuit body according to the present invention. [Figure 6] FIG. 1 is a diagram showing an example of calculation of stress relaxation rate in the present invention. [Figure 7] FIG. 1 is a diagram showing an example of calculation of stress retention in the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] [Comparison of the present invention and the prior art] In the prior art, there are materials that exhibit flexibility and restorability, but even if such materials are used as circuit films, they are not necessarily suitable. For example, when an attempt is made to make an electric circuit using a circuit film, the circuit film and the conductor circuit may not be laminated well, or the heat resistance of the electric circuit may be insufficient, resulting in deformation. Even if these requirements are met, the circuit resistance value after deformation of the electric circuit is not stable, and the operation of sensors and devices incorporating this electric circuit is not stable, making it difficult to apply the materials to sensors and devices that require precision and reproducibility. In other words, the properties of conventional materials are insufficient for applications that require precision and reproducibility, such as sensors and devices that are subject to deformation, such as wearable devices and health care devices.

[0019] In response to such problems, the present inventors have focused on the relationship between the characteristics of the circuit film and the stability of the circuit resistance value of the electric circuit body using the same, and conducted detailed studies. As a result, they have found that there is a correlation between the rheological properties of the circuit film and the stability of the circuit resistance value of the electric circuit body. The circuit film is generally made of a plastic material, and a stress relaxation phenomenon occurs when it is deformed. The speed of this stress relaxation depends on the rheological properties of the material, but in the case of a material with slow stress relaxation, the deformation of the circuit film progresses slowly even after deformation is applied. Therefore, it was found that the conductor circuit in contact with the circuit film is also subjected to this deformation, and the circuit resistance value of the electric circuit body is not easily stabilized. To solve this problem, it is effective to improve the stress relaxation speed of the circuit film used in the conductor circuit, and it was found that it is preferable that the stress relaxation phenomenon is completed or sufficiently settled immediately after deformation. As a result, the circuit resistance value after deformation of the electric circuit body is stable, and it can be used preferably for sensors and devices that are particularly prone to deformation.

[0020] Specifically, although details will be described later, it is preferable that the stress relaxation rate of the film for circuits 5 seconds after 50% strain is 0.9% / sec or less.

[0021] Furthermore, when the stability of the circuit film was examined over the time scale of actual use (for example, several minutes to several hours), it was found that the higher the stress retention rate of the circuit film after a long period of time, the better the dimensional stability of the circuit film. A high stress retention rate means that the deformation the circuit film undergoes is stored as energy, and this is thought to be due to the effect of suppressing the phenomenon of dimensional changes caused by unintended deformation from this state (for example, the neck does not return to its original shape on its own when pulled).

[0022] Specifically, it is preferable that the stress retention rate of the circuit film is 50% or more after 10 minutes at a strain of 50%. The method for measuring the stress retention rate is as described below, and the stress when the strain reaches 50% (1.5 times elongation) from the start of elongation is defined as F1, and the stress when the strain is maintained at 50% for 10 minutes is defined as F2, and the stress retention rate is calculated from the following formula. (Stress retention rate [%])=(F2 / F1)×100

[0023] Furthermore, the present inventors have studied the rigidity of the circuit film. In general, in sensors and devices that undergo deformation, it is desirable for the circuit film, which is a component thereof, to be flexible and to be able to deform freely. On the other hand, if the rigidity of the circuit film is too low, the electric circuit using the circuit film and the sensor or device incorporating it may become too flexible. In that case, when the sensor or device is deformed according to the application, it is considered that the circuit resistance value may momentarily jump up or be partially broken due to excessive deformation beyond expectation or local deformation. Therefore, a detailed study was conducted on the rigidity of the circuit film, and it was found that it is preferable that the initial stress in the stress-strain curve is equal to or higher than a certain level in order to suppress extreme deformation at the initial stage of deformation.

[0024] Specifically, the 5% strain stress of the film for circuits is preferably 1.0 MPa or more.

[0025] Furthermore, the inventors have investigated the relationship between the detailed rheological properties of the circuit film and the recovery behavior of elastic circuits, sensors and devices incorporating the circuit film.

[0026] It was found that the smaller the loss tangent, especially, of the rheological properties of the circuit film, the better the recovery of the elastic circuit and the sensor or device incorporating the circuit film. This is because the loss tangent converts the mechanical energy given from the outside into heat, which cannot be stored as elastic energy and may result in insufficient recovery behavior. In addition, as mentioned above, the mechanical energy is converted into heat, which generates heat in the circuit film and its surrounding areas, causing microscopic temperature unevenness and disturbing the recovery behavior. In particular, this phenomenon occurs in precision sensors because they are composites of organic and inorganic materials and because the circuit and product designs are precise. Therefore, in cases where a precise product design is performed or a device is required to have a high level of recovery behavior, it is considered very preferable to reduce the loss tangent of the circuit film to be incorporated.

[0027] Specifically, it is preferable that the loss tangent of the film for circuits at 25° C. and a frequency of 1 Hz is 0.25 or less.

[0028] Furthermore, the inventors have discovered that in order for the stress relaxation phenomenon to be completed or sufficiently resolved soon after the circuit film is deformed, it is advantageous for the chemical structure of the resin constituting the circuit film to have high mobility, and therefore it is preferable for the glass transition temperature to be sufficiently low.

[0029] Specifically, the glass transition temperature of the film for circuits is preferably 0° C. or lower.

[0030] [Mode of the present invention] Hereinafter, the embodiment of the present invention will be described in detail. A preferred embodiment of the circuit film of the present invention is a circuit film having a recovery of 20% or more and a stress relaxation rate of 0.9% / sec or less 5 seconds after 50% strain.

[0031] The methods for measuring the recovery property and the stress relaxation rate are as follows. How to measure resilience: With an initial chuck distance of 20 mm and a tensile speed of 300 mm / min, the test piece is stretched to a strain of 10 mm (50%), after which the tensile load on the test piece is released and the distance marked as the initial test length before the measurement is measured and regarded as L mm. The recovery rate is calculated from the following formula. Recovery rate [%] = (1-(L-20) / 10) x 100 Method for measuring stress relaxation rate at 5 seconds after 50% strain: With an initial chuck distance of 40 mm and a tensile speed of 300 mm / min, the test piece is stretched to a strain of 20 mm (50%) and held in that state for 10 minutes. The stress is measured every 1 second from the start of stretching while the strain is held at 50% for 10 minutes. The stress at x seconds after 50% strain is defined as σx and calculated using the following formula. (Stress relaxation rate at 5 seconds after 50% strain [% / sec]) = ((σ6-σ5) / σ0) × 100

[0032] The stress relaxation rate is preferably in the range of 0.9% / sec or less, more preferably 0.7% / sec or less, and particularly preferably 0.5% / sec or less.

[0033] A stress relaxation rate of 0.9% / sec or less is preferable because the stress relaxation phenomenon is completed or sufficiently settled immediately after deformation, and the slowly progressing deformation after deformation is applied in the conductor circuit in contact with the film for circuits can be suppressed, improving the stability of the circuit resistance value. On the other hand, if the stress relaxation rate exceeds 0.9% / sec, the stability of the circuit resistance value may be insufficient.

[0034] To achieve a recovery rate of 20% or more and a stress relaxation rate of 0.9% / sec or less 5 seconds after 50% strain, for example, the resin constituting the film for circuits must have a network-like crosslinked structure and the glass transition temperature of the film for circuits must be set to 0° C. or less to improve mobility. Specifically, this is possible if the resin constituting the film for circuits has the segments described below.

[0035] Furthermore, it is preferable that the circuit film of the present invention satisfies the following condition 1. Condition 1: The 5% strain stress of the circuit film is 1.0 MPa or more.

[0036] The method for measuring the 5% strain stress will be described later.

[0037] The preferred range of the 5% strain stress is 1 MPa or more, and more preferably 1.5 MPa or more.

[0038] When the strain stress at 5% elongation, which corresponds to the initial stage of deformation, is 1.0 MPa or more, the rigidity of the circuit body is improved and extreme deformation at the initial stage of deformation can be suppressed. Therefore, when a sensor or device is deformed according to the application, it is possible to suppress a momentary increase in the circuit resistance value or partial damage due to excessive deformation more than expected or localized deformation.

[0039] Furthermore, it is preferable that the circuit film of the present invention satisfies the following condition 2. Condition 2: The stress retention rate of the circuit film is 50% or more after 10 minutes with the distortion amount of the circuit film being 50%.

[0040] The method for measuring the stress retention will be described later.

[0041] The preferred range of the stress retention rate after 10 minutes at a strain of 50% is 50% or more, more preferably 60% or more, and particularly preferably 70% or more.

[0042] A stress retention rate of 50% or more after 10 minutes is preferable because it can suppress unintended deformation of a product incorporating the circuit film of the present invention. On the other hand, if the stress retention rate after 10 minutes is less than 50%, the product incorporating the circuit film may undergo unintended deformation, which may be unsuitable.

[0043] Furthermore, it is preferable that the circuit film of the present invention satisfies the following condition 3. Condition 3: At 25°C and a frequency of 1 Hz, the loss tangent of the circuit film is 0.25 or less.

[0044] The method for measuring the loss tangent will be described later.

[0045] At 25° C. and a frequency of 1 Hz, the loss tangent of the film for circuits is preferably in the range of 0.25 or less, more preferably 0.20 or less, and particularly preferably 0.10 or less.

[0046] At 25° C. and a frequency of 1 Hz, the loss tangent of the film for circuits is preferably 0.25 or less, since when a product incorporating the film for circuits of the present invention is deformed, the recovery behavior of the product is not particularly hindered. On the other hand, when the loss tangent of the film for circuits exceeds 0.25, when a product incorporating the film for circuits is deformed, the recovery behavior of the product may be hindered, making the film unsuitable for applications requiring high or precise recovery.

[0047] Furthermore, it is preferable that the circuit film of the present invention satisfies the following condition 4. Condition 4: The glass transition temperature of the circuit film is 0° C. or lower.

[0048] The method for measuring the glass transition temperature will be described later.

[0049] The glass transition temperature is preferably in the range of 0° C. or lower, more preferably −30° C. or lower.

[0050] A glass transition temperature of 0° C. or lower is preferable because the stress relaxation rate is high, whereas a glass transition temperature of more than 0° C. may result in an insufficient stress relaxation rate.

[0051] Furthermore, it is preferable that the circuit film of the present invention satisfies the following condition 5. Condition 5: The resin constituting the circuit film contains a segment of Chemical Formula 1.

[0052] Here, the segment of Chemical Formula 1 refers to a (meth)acrylic residue obtained by crosslinking a (meth)acrylic group. The circuit film of the present invention is preferable because it has a (meth)acrylic residue obtained by crosslinking a (meth)acrylic group, and therefore has improved restoring properties and stress relaxation speed. Each segment contained in the resin constituting the circuit film can be confirmed by TOF-SIMS, FT-IRR, etc.

[0053] [ka]

[0054] R 1 refers to a hydrogen or a methyl group. R 2 refers to one of the following: Substituted or unsubstituted alkylene group Substituted or unsubstituted arylene groups An alkylene group having an internal ether group, ester group, or amide group. An arylene group having an internal ether group, ester group, or amide group An unsubstituted alkylene group having an internal ether group, ester group, or amide group. An unsubstituted arylene group having an ether group, an ester group, or an amide group therein.

[0055] Furthermore, it is preferable that the circuit film of the present invention satisfies the following condition 6. Condition 6: The resin constituting the circuit film contains a segment of Chemical Formula 1 and a segment of Chemical Formula 2.

[0056] Chemical formula 1 is as described above.

[0057] Here, the segment in Chemical Formula 2 refers to a tricyclodecyl segment. The circuit film of the present invention has a three-dimensional structure that increases the rigidity of the film, and does not change the density of the crosslinked structure of the polymer that constitutes the film, so that the film does not inhibit the mobility of the entire polymer, which is preferable because it can increase the 5% strain stress while maintaining the stress relaxation rate. This is preferable because, when an electric circuit body is produced using the circuit film of the present invention, the supportability of the electric circuit body can be improved while suppressing changes in resistance value.

[0058] [ka]

[0059] n is an integer from 1 to 50.

[0060] Furthermore, the circuit film of the present invention preferably satisfies the following condition 7, more preferably satisfies condition 8, and particularly preferably satisfies condition 9. Condition 7: The resin constituting the circuit film is a resin obtained by curing component A having a segment of chemical formula 1 and component B having segments of chemical formula 1 and chemical formula 2, and component A and component B are different components. Condition 8: The resin constituting the circuit film is a resin obtained by curing a composition in which the mass ratio of component B to component A is 10% or more and 50% or less. Condition 9: The molecular weight of component B is 500 or less.

[0061] As described above, when forming the resin constituting the circuit film, it is preferable to prepare component A having a segment of chemical formula 1 and component B having segments of chemical formula 1 and chemical formula 2 separately, mix them, and harden them, since this allows the amount of the segment of chemical formula 2 in the resin constituting the circuit film to be efficiently controlled. In addition, particularly when component A is a high molecular weight substance, high molecular weight substances generally tend to have poor compatibility with other components, so it is preferable that component B has a relatively low molecular weight of 500 or less, since this can suppress separation of components A and B. In addition, from the viewpoint of the circuit film being flexible and having high restorability, having a fast stress relaxation rate, and also having appropriate rigidity, it is preferable that the resin constituting the circuit film is a resin obtained by hardening a mixture in which the mass ratio of component B to component A is 10% or more and 50% or less.

[0062] Here, when an electric circuit was produced using the circuit film of the present invention, it was found that there was an effect of suppressing the change in resistance value of the conductor circuit when the electric circuit was stretched. It is presumed that the high stress relaxation rate of the circuit film suppresses the change in dimensions over time after deformation of the electric circuit, thereby suppressing the effect of suppressing the change in resistance value of the conductor circuit when the electric circuit is stretched. In addition, this makes it suitable for use in applications such as stretchable wiring boards for health care sensors and wearable devices.

[0063] [Circuit film] The circuit film of the present invention may have other functions such as fingerprint resistance, formability, designability, scratch resistance, antifouling, antireflection, antistatic, electrical conductivity, heat reflection, near-infrared absorption, electromagnetic wave shielding, etc., in addition to the flexibility and rapid stress relaxation properties that were the objective of the film, and in this case, one or more layers may be further formed. For example, a functional layer having the above-mentioned functions, an adhesive layer, an electronic circuit layer, a printing layer, an optical adjustment layer, or other functional layers may be provided.

[0064] The thickness of the circuit film of the present invention is not particularly limited and is appropriately selected depending on the application. The lower limit of the thickness of the circuit film is not generally determined because it is affected by the elastic modulus, breaking elongation, peeling force and peeling angle from the laminate, etc. of the circuit film itself, but when the same physical properties as those of a general flexible material are realized using the manufacturing method of the laminate described later, the lower limit is about 1 μm.

[0065] [Resin precursor] The resin precursor is not particularly limited as long as it is a compound having a site capable of being crosslinked, but it preferably contains a segment of Chemical Formula 2. It is more preferable that the resin precursor contains a segment of Chemical Formula 3 or Chemical Formula 4.

[0066] [ka]

[0067] [ka]

[0068] R 3 refers to a hydrogen or a methyl group. R 4 , R 5 refers to one of the following: Substituted or unsubstituted alkylene group Substituted or unsubstituted arylene groups An alkylene group having an internal ether group, ester group, or amide group. An arylene group having an internal ether group, ester group, or amide group An unsubstituted alkylene group having an internal ether group, ester group, or amide group. An unsubstituted arylene group having an ether group, an ester group, or an amide group therein. R 6 refers to one of the following: Substituted or unsubstituted alkylene group A substituted or unsubstituted alkenylene group.

[0069] As described above, the segment of Chemical Formula 3 has a (meth)acrylic group, indicated by X in the diagram, at its end, and this (meth)acrylic group (X) at the end corresponds to a site that can be crosslinked. Furthermore, the (meth)acrylic group (X) is adjacent to a polyisocyanate residue, indicated by Y in the diagram. This also means that the other end of the urethane bond of the polyisocyanate residue, indicated by Y, is adjacent to a polyol residue, indicated by Z.

[0070] The polyisocyanate residue (Y) of Chemical Formula 3 is preferably a residue of a polyisocyanate such as TDI (tolylene diisocyanate), MDI (4,4'-diphenylmethane diisocyanate), NDI (1,5-naphthalene diisocyanate), TODI (tolidine diisocyanate), XDI (xylylene diisocyanate), PPDI (paraphenylene diisocyanate), TMXDI (tetramethylxylylene diisocyanate), HMDI (hexamethylene diisocyanate), IPDI (isophorone diisocyanate), H6XDI (hydrogenated xylylene diisocyanate), or H12MDI (dicyclohexylmethane diisocyanate).

[0071] The polyol residue of Chemical Formula 3 is preferably a polyester polyol, a polyether polyol, or a polycarbonate polyol from the viewpoint of flexibility.

[0072] Examples of polyester polyols include polyethylene adipate diol, polybutylene adipate diol, polyethylene butylene adipate diol, polyhexamethylene isophthalate adipate diol, polyethylene succinate diol, polybutylene succinate diol, polyethylene sebacate diol, polybutylene sebacate diol, poly-ε-caprolactone diol, poly(3-methyl-1,5-pentylene adipate) diol, polycondensates of 1,6-hexanediol and dimer acid, and various derivatives thereof.

[0073] The polyether polyol may be a polyalkylene glycol having two or more oxyalkylene units, and specific examples thereof include polyalkylene glycols such as polyethylene glycol, polypropylene glycol, and polytetramethylene glycol, and various derivatives thereof.

[0074] Examples of polycarbonate polyols include reaction products of carbonates and glycols. Specific examples of carbonates include diaryl carbonates such as diphenyl carbonate, dialkyl carbonates such as dimethyl carbonate and diethyl carbonate, ethylene carbonate, diphenyl phenyl carbonate, and phosgene. Examples of diols include ethylene glycol, propylene glycol, butanediol, 1,5-pentanediol, 1,6-hexanediol, 2-methyl-1,8-octanediol, nonanediol, cyclohexanedimethanol, neopentyl glycol, 3-methyl-1,5-pentanediol, hydroxypivalic acid neopentyl glycol ester, and various derivatives thereof.

[0075] [Laminate] The film for circuits of the present invention may form a laminate having a supporting substrate on one side thereof. The laminate is preferably a laminate in which the peel strength between the supporting substrate and the film for circuits is 1 N / 50 mm or less. Hereinafter, a supporting substrate having a peel strength of 1 N / 50 mm or less from the film for circuits will be referred to as a peelable supporting substrate.

[0076] As described above, in the laminate of the present invention, the peel strength between the support substrate and the film for circuits is preferably 1 N / 50 mm or less, and more preferably 800 mN / 50 mm or less. There is no particular lower limit to the peel strength between the support substrate and the film for circuits, but if it is less than 10 mN / 50 mm, the support substrate and the film for circuits may peel off or float during the manufacturing process, so the peel strength between the support substrate and the film for circuits is preferably 10 mN / 50 mm or more.

[0077] [Supporting base material] The support substrate used in the laminate may be any of a thermoplastic resin and a thermosetting resin, and may be a homogeneous resin, a copolymer, or a blend of two or more kinds. The resin constituting the support substrate is preferably one having good moldability, and from this point of view, a thermoplastic resin is more preferable.

[0078] Examples of thermoplastic resins that can be used include polyolefin resins such as polyethylene, polypropylene, polystyrene, and polymethylpentene, alicyclic polyolefin resins, polyamide resins such as nylon 6 and nylon 66, aramid resins, polyimide resins, polyester resins, polycarbonate resins, polyarylate resins, polyacetal resins, polyphenylene sulfide resins, fluororesins such as tetrafluoroethylene resin, trifluoroethylene resin, trichloroethylene resin, tetrafluoroethylene-hexafluoropropylene copolymer, and vinylidene fluoride resin, acrylic resins, methacrylic resins, polyacetal resins, polyglycolic acid resins, and polylactic acid resins.

[0079] Examples of the thermosetting resin that can be used include phenol resin, epoxy resin, urea resin, melamine resin, unsaturated polyester resin, polyurethane resin, polyimide resin, and silicone resin.

[0080] The thermoplastic resin is preferably a resin having sufficient stretchability and conformability. From the viewpoints of strength, heat resistance, and transparency, the thermoplastic resin is more preferably a polyester resin, a polycarbonate resin, an acrylic resin, or a methacrylic resin.

[0081] The polyester resin in the present invention is a general term for a polymer having an ester bond as the main bond in the main chain, and is obtained by polycondensation of an acid component and its ester with a diol component. Specific examples include polyethylene terephthalate, polypropylene terephthalate, polyethylene-2,6-naphthalate, and polybutylene terephthalate. These may also be copolymerized with other dicarboxylic acids and their esters or diol components as the acid component or diol component. Among these, polyethylene terephthalate and polyethylene-2,6-naphthalate are particularly preferred in terms of transparency, dimensional stability, heat resistance, and the like.

[0082] In addition, the supporting substrate may contain various additives, such as an antioxidant, an antistatic agent, a crystal nucleating agent, inorganic particles, organic particles, a viscosity reducer, a heat stabilizer, a lubricant, an infrared absorber, an ultraviolet absorber, and a dopant for adjusting the refractive index.

[0083] Furthermore, the supporting substrate may have either a single layer structure or a laminate structure.

[0084] In addition, a functional layer such as an easy-adhesion layer, an antistatic layer, an undercoat layer, an ultraviolet absorbing layer, or a release layer may be provided on the surface of the support substrate in advance, in addition to the film for circuits of the present invention, and in the present invention, the support substrate preferably has a release layer in order to reduce the peeling force between the support substrate and the film for circuits. The details of the release layer will be described later.

[0085] Examples of supporting substrates provided with a release layer include "Therapeel" (registered trademark) manufactured by Toray Advanced Film Co., Ltd., "Unipeel" (registered trademark) manufactured by Unitika Ltd., "Panapeel" (registered trademark) manufactured by Panac Corporation, "Toyobo Ester" (registered trademark) manufactured by Toyobo Co., Ltd., and "Purex" (registered trademark) manufactured by Teijin Limited, and these products can also be used.

[0086] The surface of the supporting substrate may be subjected to various surface treatments before the circuit film is formed. Examples of surface treatments include chemical treatment, mechanical treatment, corona discharge treatment, flame treatment, ultraviolet irradiation treatment, high frequency treatment, glow discharge treatment, active plasma treatment, laser treatment, sandblasting treatment, mixed acid treatment, and ozone oxidation treatment. Among these, glow discharge treatment, ultraviolet irradiation treatment, corona discharge treatment, and flame treatment are preferred, and glow discharge treatment and ultraviolet treatment are more preferred.

[0087] [Release layer] The support substrate used in the laminate preferably has a release layer. A support substrate having a release layer is also called a release film. The release layer may be composed of a plurality of layers from the viewpoint of imparting adhesion, antistatic properties, solvent resistance, etc., and may be present on both sides of the support substrate.

[0088] The composition and thickness of the release layer are not particularly limited as long as the peel strength from the circuit film can be within the preferred range described above. From the standpoint of the in-plane uniformity, quality, and peel strength of the release layer, however, it is preferably 10 nm or more and 500 nm or less, and more preferably 20 nm or more and 300 nm or less.

[0089] [Protective material] The laminate may have a protective material on the surface of the circuit film opposite to the supporting substrate as shown in FIG. 3. The protective material and the supporting substrate are distinguished in that, in the manufacturing method of the laminate, the one to which the coating composition is applied is the supporting substrate, and the one to which the circuit film is formed is the protective material. The protective material may be the same as or different from the supporting substrate, but it is preferable that the protective material has a different peeling force from the supporting substrate when used in a later process. The magnitude relationship between the peeling force of the protective material and the supporting substrate from the circuit film is appropriately selected depending on the method of use in the later process. Therefore, the protective material may have a release layer, may have an adhesive layer, or may be a single layer.

[0090] [Manufacturing method of film for circuits] The method for producing the circuit film of the present invention is not particularly limited, but preferably includes the steps of applying a coating composition containing a resin precursor containing a segment of Chemical Formula 2, Chemical Formula 3, or Chemical Formula 4 onto a supporting substrate to form a coating layer (step 1), then removing the solvent from the coating layer and drying it (step 2), irradiating it with active energy rays to crosslink the resin precursor (step 3), and peeling the supporting substrate from the laminate (step 4).

[0091] Furthermore, it is preferable that, after the above-mentioned "step 3", a step of applying a coating composition for a particle layer containing particles and a resin component to form a coating layer and a step of removing the solvent from the coating layer are carried out in this order, or, after "step 3", a step of applying a coating composition for a particle layer containing particles and a resin precursor to form a coating layer, a step of removing the solvent from the coating layer, and a step of irradiating with active energy rays to crosslink the resin precursor and form a laminate having a circuit film on a supporting substrate are carried out in this order.

[0092] Furthermore, when a supporting substrate having a surface shape such as a concave-convex shape is used as the supporting substrate, it is possible to form a surface shape on the surface of the film for circuits by transferring the surface shape such as a concave-convex shape of the supporting substrate to the surface of the film for circuits obtained in the above-mentioned "step 4" that was in contact with the supporting substrate. At this time, the surface shape of the supporting substrate and the surface shape of the film for circuits are inverted.

[0093] The method of applying the coating composition onto the supporting substrate in step 1 is not particularly limited as long as the coating composition can be applied onto the supporting substrate to form a uniform coating layer in the plane. The coating method onto the supporting substrate can be appropriately selected from a dip coating method, a roller coating method, a wire bar coating method, a gravure coating method, a die coating method (US Pat. No. 2,681,294), and the like. Here, the coating layer refers to a "liquid layer" formed by the coating step.

[0094] The method for removing the solvent in step 2, i.e., the drying method, is not particularly limited as long as it can remove the solvent from the coating layer formed on the support substrate. Drying methods include heat transfer drying (contact with a high-heat object), convection heat transfer (hot air), radiation heat transfer (infrared rays), and others (microwaves, induction heating), and among these, in the manufacturing method of the present invention, a method using convection heat transfer or radiation heat transfer is preferred because it is necessary to precisely make the drying speed uniform even in the width direction.

[0095] The crosslinking method in step 3 involves irradiating the coating layer from which the solvent has been removed after drying with active energy rays to cause a reaction and crosslink the coating film.

[0096] Crosslinking by active energy rays is preferably performed using electron beams (EB) and / or ultraviolet rays (UV) from the viewpoint of versatility. Examples of the type of ultraviolet lamp used for irradiating ultraviolet rays include discharge lamp type, flash type, laser type, and electrodeless lamp type. When ultraviolet curing is performed using a high-pressure mercury lamp, which is a discharge lamp type, the illuminance of the ultraviolet rays is 100 to 3,000 (mW / cm 2 ), and more preferably 200 to 2,000 (mW / cm 2 ), and more preferably 300 to 1,500 (mW / cm 2 ), and the integrated amount of ultraviolet light is 100 to 3,000 (mJ / cm 2 ), and more preferably 200 to 2,000 (mJ / cm 2 ), and more preferably 300 to 1,500 (mJ / cm 2 ) where UV illuminance is the radiation intensity received per unit area, and varies with lamp output, light emission spectral efficiency, diameter of the light emitting bulb, design of the reflector, and the distance between the irradiated object and the light source. However, illuminance does not vary with transport speed. Additionally, the integrated UV light quantity is the radiation energy received per unit area, and is the total amount of photons that reach the surface. The integrated light quantity is inversely proportional to the radiation speed passing under the light source, and proportional to the number of irradiations and the number of lamps.

[0097] [Paint composition] The "coating composition" used in the aforementioned method for producing a film for circuits is not particularly limited as long as it can be uniformly applied on the surface of the supporting substrate and can form a film for circuits exhibiting the characteristics of the present invention, but it is preferable that the coating composition is suitable for the aforementioned method for producing a laminate. Specifically, it is preferable to prepare a coating composition by adding the aforementioned resin precursor to the solvent and other components described below.

[0098] [solvent] The coating composition used in the above-mentioned method for producing a film for circuits may contain a solvent, and it is preferable to contain a solvent in order to form a coating layer uniformly in the plane. The number of types of solvents is preferably 1 to 20, more preferably 1 to 10, even more preferably 1 to 6, and particularly preferably 1 to 4.

[0099] The term "solvent" as used herein refers to a substance that is liquid at room temperature and pressure and can be evaporated in its entirety in the drying step described above.

[0100] Here, the type of solvent is determined by the molecular structure that constitutes the solvent. In other words, solvents that have the same elemental composition and the same type and number of functional groups but different bond relationships (structural isomers), and solvents that are not structural isomers but do not overlap exactly in any conformation in three-dimensional space (stereoisomers) are treated as different types of solvents. For example, 2-propanol and n-propanol are treated as different solvents. Furthermore, when a solvent is included, it is preferable that the solvent exhibits the following characteristics. Property 1: When solvent B is the solvent with the lowest relative evaporation rate (ASTM D3539-87(2004)) based on n-butyl acetate, the relative evaporation rate of solvent B is 0.4 or less.

[0101] Here, the relative evaporation rate based on the solvent n-butyl acetate is the evaporation rate measured in accordance with ASTM D3539-87 (2004). Specifically, it is a value defined as the relative value of the evaporation rate based on the time required for 90% by mass of n-butyl acetate to evaporate in dry air.

[0102] If the relative evaporation rate of the solvent is greater than 0.4, the time required for the orientation of the polysiloxane segments and / or polydimethylsiloxane segments and the fluorine compound segments to the outermost surface in the resin layer A will be shortened, which may result in a decrease in the solvent resistance of the resin layer A in the obtained laminate. In addition, the lower limit of the relative evaporation rate of the solvent is not a problem as long as it is a solvent that can be evaporated and removed from the coating film in the drying process, and in a general coating process, it is sufficient if it is 0.005 or more.

[0103] Solvents include isobutyl ketone (relative evaporation rate: 0.2), isophorone (relative evaporation rate: 0.026), diethylene glycol monobutyl ether (relative evaporation rate: 0.004), diacetone alcohol (relative evaporation rate: 0.15), oleyl alcohol (relative evaporation rate: 0.003), ethylene glycol monoethyl ether acetate (relative evaporation rate: 0.2), nonylphenoxyethanol (relative evaporation rate: 0.25), propylene glycol monoethyl ether (relative evaporation rate: 0.1), and cyclohexanone (relative evaporation rate: 0.32).

[0104] [Other components in the coating composition] The coating composition used in the above-mentioned method for producing a film for circuits preferably contains an antioxidant, a polymerization initiator, a curing agent, and a catalyst. The polymerization initiator and catalyst are used to promote crosslinking of the film for circuits. The polymerization initiator is preferably one that can initiate or promote polymerization, condensation, or crosslinking reaction of the components contained in the coating composition by anionic, cationic, or radical polymerization reaction, etc.

[0105] Antioxidants are roughly classified into radical chain initiation inhibitors, radical scavengers, and peroxide decomposers based on their mechanism of action. Any of these can achieve the effect of the present invention in terms of inhibiting deterioration under high temperature conditions, which is the object of the present invention. However, radical scavengers or peroxide decomposers are more preferred, and hindered phenol-based or semi-hindered phenol-based radical scavengers, or phosphite-based or thioether-based peroxide decomposers are particularly preferred.

[0106] Various polymerization initiators, curing agents, and catalysts can be used. The polymerization initiators, curing agents, and catalysts may be used alone, or multiple polymerization initiators, curing agents, and catalysts may be used simultaneously. Furthermore, an acid catalyst or a thermal polymerization initiator may be used in combination. Examples of acid catalysts include hydrochloric acid aqueous solution, formic acid, and acetic acid. Examples of thermal polymerization initiators include peroxides and azo compounds. Examples of photopolymerization initiators include alkylphenone compounds, sulfur-containing compounds, acylphosphine oxide compounds, and amine compounds. Examples of crosslinking catalysts that promote the reaction of forming urethane bonds include dibutyltin dilaurate and dibutyltin diethylhexoate.

[0107] As the photopolymerization initiator, an alkylphenone compound is preferable from the viewpoint of curability. Specific examples of the alkylphenone compound include 1-hydroxy-cyclohexyl-phenyl-ketone, 2,2-dimethoxy-1,2-diphenylethane-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-phenyl)-1-butane, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-(4-phenyl)-1-butane, 2-benzyl-2-dimethylamino-1-(4- morpholinophenyl)-1-butane, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butane, 1-cyclohexyl-phenyl ketone, 2-methyl-1-phenylpropan-1-one, 1-[4-(2-ethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, bis(2-phenyl-2-oxoacetate)oxybisethylene, and polymerized versions of these materials.

[0108] Furthermore, a leveling agent, a lubricant, an antistatic agent, etc. may be added to the coating composition used to form the film for circuits, so long as the effects of the present invention are not impaired. As a result, the film for circuits can contain the leveling agent, the lubricant, the antistatic agent, etc.

[0109] Examples of the leveling agent include acrylic copolymers, silicone-based, and fluorine-based leveling agents. Examples of the antistatic agent include metal salts such as lithium salts, sodium salts, potassium salts, rubidium salts, cesium salts, magnesium salts, and calcium salts.

[0110] [Application example] The circuit film of the present invention has flexibility and a high stress relaxation rate, and can be suitably used for various applications.

[0111] For example, the material can be suitably used for in-vehicle devices, wearable devices, components for healthcare devices, automobile parts, stretchable sensors, and stretchable actuators.

[0112] In addition, from the viewpoint of flexibility and high stress relaxation speed, it can be suitably used for surface materials, internal materials, constituent materials, and manufacturing process materials for adhesive tape substrates that require recovery, shock absorbing materials for displays, medical film substrates, surface protection film substrates for automobiles, core materials for pressure sensors, plastic molded products such as glasses and sunglasses, cosmetic boxes, and food containers, aquariums, showcases for exhibitions, smartphone housings, touch panels, color filters, flat panel displays, flexible displays, flexible devices, sensors, circuit materials, electrical and electronic applications, home appliances such as keyboards and remote controls for televisions and air conditioners, mirrors, window glass, buildings, dashboards, car navigation touch panels, vehicle parts such as room mirrors and windows, and various printed materials, medical films, films for sanitary materials, medical films, agricultural films, and building materials.

[0113] Furthermore, the composition can be suitably used for applications involving roll-to-roll processes, such as films, adhesive tapes, various functional film substrates, sensor materials, shock absorbing materials, vibration absorbing materials, cushioning materials, and sealing materials. EXAMPLES

[0114] The present invention will now be described with reference to examples, but the present invention is not necessarily limited to these. The components and abbreviations used in the examples and comparative examples are as follows.

[0115] [Ingredients, abbreviations] [Diisocyanate] IPDI: Isophorone diisocyanate [Polyol] PTMG: Polytetramethylene glycol, Mitsubishi Chemical Corporation PTMG2000 (weight average molecular weight 2000) PBA: Polybutylene adipate, Tosoh Corporation "Nipporun" (registered trademark) 3027

[0116] [Hydroxy acrylate] 4HBA: 4 Hydroxybutyl Acrylate. ·HEA: Hydroxyethyl acrylate

[0117] [Urethane acrylate] [Urethane acrylate 1] A four-neck flask equipped with a thermometer, a stirrer, a water-cooled condenser, and a nitrogen gas inlet was charged with 0.43 mol % IPDI as a diisocyanate and 0.29 mol PTMG as a polyol, diluted with toluene to a solids concentration of 60 mass%, and reacted at 90°C. When the residual isocyanate groups reached 1.4 mass% of the initial amount added, the temperature was lowered to 70°C, and 0.29 mol of 4HBA was added as a hydroxyacrylate to react. When the residual isocyanate groups reached 0.3 mass% of the initial amount added, the reaction was terminated, and toluene was added to adjust the solids concentration to 60 mass%, thereby obtaining a toluene solution of urethane acrylate 1.

[0118] [Urethane acrylate 2] A four-neck flask equipped with a thermometer, a stirrer, a water-cooled condenser, and a nitrogen gas inlet was charged with 0.43 mol% isophorone diisocyanate and 0.29 mol% PBA as a polyol, diluted with toluene to a solids concentration of 60 mass%, and reacted at 90°C. When the residual isocyanate groups reached 1.4 mass% of the initial amount added, the temperature was lowered to 70°C, and 0.29 mol% HEA was added as a hydroxyacrylate to react. When the residual isocyanate groups reached 0.3 mass% of the initial amount added, the reaction was terminated, and toluene was added to adjust the solids concentration to 60 mass%, thereby obtaining a toluene solution of urethane acrylate 2.

[0119] [Acrylate] [Acrylate 1] As acrylate 1, "Light Acrylate" (registered trademark) EC-A (ethoxy-diethylene glycol acrylate manufactured by Kyoeisha Chemical Co., Ltd.) was used.

[0120] [Acrylate 2] As acrylate 2, IRR-214K (tricyclodecane dimethanol diacrylate, manufactured by Daicel Allnex) was used.

[0121] [Acrylate 3] As acrylate 3, "Viscoat" V#310HP (tripropylene glycol diacrylate manufactured by Osaka Organic Chemical Industry Co., Ltd.) was used.

[0122] [Acrylate 4] As acrylate 4, tetraethylene glycol diacrylate was used.

[0123] [Photoradical polymerization initiator] [Photoradical polymerization initiator 1] As the photoradical polymerization initiator 1, "Omnirad" (registered trademark) 184 (manufactured by IGM Group BV) was used.

[0124] [Paint composition formulation] [Paint composition 1] The following materials were mixed in the following ratios and diluted with methyl ethyl ketone to obtain a coating composition 1 having a solids concentration of 30 mass %. Urethane acrylate 1: 40 parts by weight Acrylate 1: 10 parts by weight Photoradical polymerization initiator 1: 1.5 parts by mass.

[0125] [Paint composition 2] The following materials were mixed and diluted with methyl ethyl ketone to obtain coating composition 2 having a solids concentration of 30 mass %. Urethane acrylate 1: 35 parts by weight Acrylate 2: 15 parts by weight Photoradical polymerization initiator 1: 1.5 parts by mass.

[0126] [Paint composition 3] The following materials were mixed and diluted with methyl ethyl ketone to obtain coating composition 3 having a solids concentration of 30 mass %. Urethane acrylate 1: 42.5 parts by weight Acrylate 2: 7.5 parts by weight Photoradical polymerization initiator 1: 1.5 parts by mass.

[0127] [Paint composition 4] The following materials were mixed and diluted with methyl ethyl ketone to obtain coating composition 4 having a solids concentration of 30 mass %. Urethane acrylate 1: 42.5 parts by weight Acrylate 3: 7.5 parts by weight Photoradical polymerization initiator 1: 1.5 parts by mass.

[0128] [Paint composition 5] The following materials were mixed and diluted with methyl ethyl ketone to obtain coating composition 5 having a solids concentration of 30 mass %. Urethane acrylate 1: 37.5 parts by weight Acrylate 3: 12.5 parts by weight Photoradical polymerization initiator 1: 1.5 parts by mass.

[0129] [Paint composition 6] The following materials were mixed and diluted with methyl ethyl ketone to obtain coating composition 6 having a solids concentration of 30 mass %. Urethane acrylate 1: 35 parts by weight Acrylate 4: 15 parts by weight Photoradical polymerization initiator 1: 1.5 parts by mass.

[0130] [Paint composition 7] The following materials were mixed and diluted with methyl ethyl ketone to obtain coating composition 7 having a solids concentration of 30 mass %. Urethane acrylate 2: 35 parts by weight Acrylate 4: 15 parts by weight Photoradical polymerization initiator 1: 1.5 parts by mass.

[0131] [Paint composition 8] The following materials were mixed and diluted with methyl ethyl ketone to obtain coating composition 8 having a solids concentration of 30 mass %. Urethane acrylate 1: 47.5 parts by weight Acrylate 2: 2.5 parts by weight Photoradical polymerization initiator 1: 1.5 parts by mass.

[0132] [Release film] [Release film 1] As the release film 1, "Cerapeel" (registered trademark) SY (thickness 38 μm, manufactured by Toray Advanced Film Co., Ltd.) was used.

[0133] [Thermoplastic urethane film] [Thermoplastic urethane film 1] As the thermoplastic urethane film 1, "ESMER" (registered trademark) URS PX98 (thickness 150 μm, manufactured by Nihon Matai Co., Ltd.) was used.

[0134] In addition, when the composition of "Esmer" (registered trademark) URS PX98 was confirmed, it was found to be composed of a 50 μm thick polyester film layer, a 150 μm thick thermoplastic urethane film layer, and a 75 μm thick polyester film layer laminated in that order. Therefore, the 50 μm thick polyester film and the 75 μm thick polyester film were peeled off, and the thermoplastic urethane film was treated as a film for circuits.

[0135] [Thermoplastic urethane film 2] As the thermoplastic urethane film 2, "Higress" (registered trademark) DUS202-CDR (thickness 100 μm, manufactured by Seedam Co., Ltd.) was used.

[0136] When the composition of "Higress" (registered trademark) DUS202-CDR was checked, it was found to be composed of a 50 μm thick paper layer and a 100 μm thick thermoplastic urethane film layer. Therefore, the 50 μm paper was peeled off, and the thermoplastic urethane film was used as the circuit film.

[0137] [Forming film for circuits] A laminate was formed on a release film by using the above-mentioned resin layer coating composition in the combination shown in the table and the below-mentioned method for forming a resin layer.

[0138] [Method 1 for forming resin layer] [Process 1] In step 1, the above-mentioned resin layer coating composition was applied to the release layer side of the release film using a continuous coating device with a slot die coater, while adjusting the discharge flow rate so that the thickness of the circuit film after crosslinking would be the film thickness shown in the table, to form a coating layer.

[0139] [Process 2] In step 2, the coating layer formed in step 1 was dried under the following conditions to remove the solvent. ·Blow temperature: Temperature: 80℃. ·Wind speed: Application side: 5m / sec, non-application side: 5m / sec. Air direction: coated side: parallel to the surface of the substrate, non-coated side: perpendicular to the surface of the substrate. Residence time: 2 minutes.

[0140] [Step 3] In step 3, the coating layer (uncrosslinked resin layer) obtained by removing the solvent was crosslinked by irradiating it with active energy rays under the conditions described below to obtain a laminate as a film for circuits. · Light source: High pressure mercury lamp. Radiation output: 400W / cm 2 . Accumulated light output: 120mJ / cm 2 . Oxygen concentration: 0.1% by volume.

[0141] [How to make circuit film] The release film was peeled off from the laminate produced by the above method to produce films for circuits of Examples 1 to 8. In addition, as Comparative Examples 1 and 2, thermoplastic urethane films 1 and 2 were used.

[0142] The table also lists whether each segment of each chemical formula of the film for circuits is included or not.

[0143] For Comparative Examples 1 and 2, whether each segment was contained was confirmed by TOF-SIMS and FT-IR.

[0144] In the table, "includes" in each column for Chemical Formula 1 means that the circuit film in each example contains a segment of Chemical Formula 1, and "does not include" means that the circuit film in each example does not contain a segment of Chemical Formula 1.

[0145] [Table 1]

[0146] [Evaluation of film for circuits] The following performance evaluations were carried out on the film for circuits. Unless otherwise specified, measurements were taken three times for one sample in each example at different locations, and the average value was used.

[0147] [Thickness of circuit film] The thickness of the circuit film was measured by observing the cross section using a scanning electron microscope (SEM) according to the following method. The layer thickness was read from an image of a cross-section of the circuit film taken with an SEM at 3,000 times magnification using software (image processing software ImageJ). The layer thickness was measured at a total of 30 points, and the average value was used as the measured value.

[0148] [Recovery rate] After cutting the laminate into a rectangle of 10 mm width x 150 mm length, the circuit film was peeled off from the support substrate to prepare a test specimen. The 150 mm length was aligned with the longitudinal direction of the laminate. Using a tensile tester (Universal Material Tester RTG-1210 manufactured by A&D Co., Ltd.), the initial chuck distance was set to 20 mm, the tensile speed was set to 300 mm / min, and the test specimen was stretched to a strain of 10 mm (50%), after which the tensile load on the test specimen was released, and the distance marked as the initial test length before the measurement was measured and defined as L mm, and the recovery rate was calculated from the following formula. The measurement was performed at a temperature of 23°C and a humidity of 65% RH. Recovery rate [%] = (1-(L-20) / 10) x 100

[0149] [Stress relaxation rate] The laminate was cut into a rectangle of 10 mm width x 140 mm length, and the circuit film was peeled off from the support substrate to prepare a test piece. The 150 mm length was aligned with the longitudinal direction of the laminate. Using a tensile tester (Universal Material Tester RTG-1210 manufactured by A&D Co., Ltd.), the initial chuck distance was set to 40 mm, the tensile speed was set to 300 mm / min, and the measurement temperature was 23°C and the humidity was 65% RH. The test piece was stretched to a strain of 20 mm (50%) and held in that state for 10 minutes. The stress was measured every 1 second from the start of stretching until the strain was held at 50% for 10 minutes.

[0150] The stress at x seconds after 50% strain was defined as σx, and the stress relaxation rate at 5 seconds after 50% strain was calculated from the following formula. (Stress relaxation rate at 5 seconds after 50% strain [% / sec]) = ((σ6-σ5) / σ0) × 100

[0151] However, if any of the stress relaxation rates from 1 second to 5 seconds after strain was below 0, it was determined that stress relaxation had already been completed, and the stress relaxation rate [% / sec] 5 seconds after 50% strain was treated as 0.

[0152] [Stress retention rate] The laminate was cut into a rectangle of 10 mm width x 140 mm length, and the circuit film was peeled off from the support substrate to prepare a test piece. The 150 mm length was aligned with the longitudinal direction of the laminate. Using a tensile tester (Universal Material Tester RTG-1210 manufactured by A&D Co., Ltd.), the initial chuck distance was set to 40 mm, the tensile speed was set to 300 mm / min, and the measurement temperature was 23°C and the humidity was 65% RH. The test piece was stretched to a strain of 20 mm (50%) and held in that state for 10 minutes. The stress was measured every 1 second from the start of stretching until the strain was held at 50% for 10 minutes.

[0153] The stress when the strain reached 50% from the start of elongation was defined as F1, and the stress when the strain was maintained at 50% for 10 minutes was defined as F2. The stress retention rate was calculated from the following formula. (Stress retention rate [%])=(F2 / F1)×100

[0154] [5% strain stress] The laminate was cut into a rectangle of 10 mm width x 150 mm length, and the circuit film was peeled off from the support substrate to prepare a test piece. The 150 mm length was aligned with the longitudinal direction of the laminate. Using a tensile tester (A&D Co., Ltd. Universal Material Tester RTG-1210), the initial tensile chuck distance was set to 50 mm, the tensile speed was set to 300 mm / min, and the measurement temperature was 23°C and the humidity was 65% RH.

[0155] Read the load b (N) applied to the sample when the chuck distance is a (mm), and use the following formula to calculate the strain [%] and stress y [MPa = N / mm 2 ] was calculated, where k [mm] is the sample thickness before the test. (Strain amount) = ((a-50) / 50) x 100 (stress)=b / (k×10).

[0156] Of the data obtained above, the stress at a strain of 5% was defined as the 5% strain stress.

[0157] [Glass transition temperature, loss tangent] Based on the tensile vibration non-resonance method of JIS K7244 (1998) (this is called the dynamic viscoelasticity method), the storage modulus and loss modulus of the circuit film were determined using a dynamic viscoelasticity measuring device DMS6100 manufactured by Seiko Instruments Inc. The loss tangent was calculated from the obtained values, and a curve of temperature vs. loss tangent was plotted, and the temperature at which the loss tangent showed a maximum value was determined as the glass transition temperature.

[0158] In addition, when there are multiple temperatures at which the loss tangent shows a maximum value, the temperature at which the loss tangent shows a maximum value in a temperature range where the storage modulus is 10 MPa or more is prioritized as the glass transition temperature, and when the temperature at which the loss tangent shows a maximum value is still not determined to be a single point, the temperature at which the loss tangent shows the largest value is prioritized as the glass transition temperature. Measurement mode: Tensile Chuck distance: 20mm Test piece width: 10mm Frequency: 1Hz Distortion amplitude: 10μm Initial force amplitude: 40mN Measurement temperature: -100℃ to 100℃ Heating rate: 5℃ / min Loss tangent: (Loss modulus) / (Storage modulus).

[0159] [Evaluation of stability of circuit resistance value] The stability of the circuit resistance value was evaluated by a method in which the electric circuit body on which the circuit wiring was formed was stretched by a tensile tester while measuring the resistance value by a digital multimeter.

[0160] <Creating test pieces> A screen plate (100×100 SUS325-28-C NU-55 emulsion thickness 5 μm manufactured by Nakanuma Art Screen Co., Ltd.) having a wiring pattern with a straight line portion of 1 mm width and 50 mm length between the electrode parts shown in FIG. 5 was attached to a small screen printing machine (LS-150 manufactured by Newlong Precision Industry Co., Ltd.), and a printing paste (LS-453-6B manufactured by Asahi Chemical Research Institute Co., Ltd.) was placed on the screen plate. Next, the circuit film was fixed on the printing machine stage, and a wiring pattern was printed on the surface. After that, it was dried at 80° C. for 30 minutes to create an electric circuit body. The electric circuit body was cut out to a width of 20 mm and a length of 150 mm with this wiring pattern as the center, and used as a test piece. The direction of the 150 mm length was aligned with the longitudinal direction of the circuit film.

[0161] <Measurement> A 30 mm square copper plate was brought into contact with the electrode of the test piece and fixed with tape. This test piece and copper plate were connected to a tensile testing machine (Universal Material Tester RTG-1210 manufactured by A&D Co., Ltd.). The distance between the chucks was set to 50 mm, and was adjusted so that the distance between the chucks and the straight section were aligned. The copper plate was connected to a digital multimeter (Keysight Technologies "Digital Multimeter" 34465A) via a clip. While recording the resistance value with the digital multimeter, the sample was stretched to a strain of 20% at a tensile speed of 100 mm / min and held for 10 seconds.

[0162] When the longitudinal direction was unknown, a sample was prepared in an arbitrary direction, and then samples were prepared at 60° and 120° rotations, and the measurement results of a total of three samples were averaged for evaluation.

[0163] The initial resistance value (= 0% strain) was defined as R1 [Ω], and the resistance value 5 seconds after 20% strain was reached was defined as R2 [Ω]. The resistance change rate [%] was calculated using the following formula. (Resistance change rate) = (R2-R1 / R1) x 100

[0164] <Judgment> The evaluation was made according to the following criteria. 10 points: Resistance change rate is 130% or less. 7 points: Resistance change rate is over 130% but not more than 140%. 4 points: Resistance change rate is between 140% and 160%. 1 point: Other (resistance change rate exceeds 160%, etc.).

[0165] [Evaluation of supportability] The film for circuits was pulled by hand in a room temperature environment and evaluated according to the following criteria. 10 points: No deformation even with very light pressure. 7 points: Can be deformed with a moderate amount of force. 4 points: Can be deformed with light pressure. 1 point: Other (deforms with very light force, etc.).

[0166] [Evaluation of dimensional stability] In a room temperature environment, the circuit film was stretched by 50% by hand and held for 1 minute. The dimensions after stretching were used as the standard for observation and evaluation according to the following criteria. 10 points: No deformation from dimensions after 50% tension. 7 points: Slight deformation from the dimensions after 50% tension. 4 points: There is a slight deformation from the dimensions after 50% tension. 1 point: Other (significant deformation from the dimensions after 50% tension, wrinkles, etc.).

[0167] The evaluation results of each of the Examples and Comparative Examples are summarized in the table.

[0168] [Table 2]

[0169] [Table 3] [Explanation of symbols]

[0170] 1 Circuit Film 2 Circuit Film 3 Release film 4 Protective material 5 Circuit Film 6 Release film 11 Electrical circuit body 12 Circuit Film 13 Electrical Circuits 21 Circuit Film 22 Wiring circuit 23 Electrode section 24 Electrical circuit body 31 Holding time after reaching 50% strain [sec] 32 Stress [MPa] 33 Stress retention curve [MPa] 34 Stress at x seconds after reaching 50% strain [MPa] 41 Holding time after reaching 50% strain [min] 42 Stress [MPa] 43 Stress retention curve [MPa] 44 Stress F2 [MPa] 10 minutes after reaching 50% strain 45 Stress F1 [MPa] immediately after strain reaches 50% [Industrial Applicability]

[0171] The circuit film of the present invention has flexibility and a high stress relaxation rate, and can be suitably used for various applications.

[0172] For example, the material can be suitably used for in-vehicle devices, wearable devices, components for healthcare devices, automobile parts, stretchable sensors, and stretchable actuators.

[0173] In addition, from the viewpoint of flexibility and high stress relaxation speed, it can be suitably used for surface materials, internal materials, constituent materials, and manufacturing process materials for adhesive tape substrates that require recovery, shock absorbing materials for displays, medical film substrates, surface protection film substrates for automobiles, core materials for pressure sensors, plastic molded products such as glasses and sunglasses, cosmetic boxes, and food containers, aquariums, showcases for exhibitions, smartphone housings, touch panels, color filters, flat panel displays, flexible displays, flexible devices, sensors, circuit materials, electrical and electronic applications, home appliances such as keyboards and remote controls for televisions and air conditioners, mirrors, window glass, buildings, dashboards, car navigation touch panels, vehicle parts such as room mirrors and windows, and various printed materials, medical films, films for sanitary materials, medical films, agricultural films, and building materials.

[0174] Furthermore, the composition can be suitably used for applications involving roll-to-roll processes, such as films, adhesive tapes, various functional film substrates, sensor materials, shock absorbing materials, vibration absorbing materials, cushioning materials, and sealing materials.

Claims

1. A film for circuits having a restoration rate of 20% or more, The stress relaxation rate at 5 seconds after 50% strain is 0.9% / sec or less. Film for circuits. How to measure resilience: The test piece was stretched to a strain of 10 mm (50%) with an initial chuck distance of 20 mm and a tensile speed of 300 mm / min, and then the tensile load on the test piece was released. The distance marked as the initial test length before the measurement was measured and defined as L mm, and the recovery rate was calculated from the following formula. Recovery rate [%] = (1 - (L - 20) / 10) x 100 Method for measuring stress relaxation rate at 5 seconds after 50% strain: The test piece is stretched to a strain of 20 mm (50%) with an initial chuck distance of 40 mm and a tensile speed of 300 mm / min, and held in that state for 10 minutes. The stress is measured every 1 second from the start of stretching until the strain of 50% is held for 10 minutes. The stress at x seconds after 50% strain is defined as σx, and calculated from the following formula. (Stress relaxation rate at 5 seconds after 50% strain [% / sec])=((σ6-σ5) / σ0)×100

2. The circuit film according to claim 1 , which satisfies the following condition 1: Condition 1: The 5% strain stress of the circuit film is 1.0 MPa or more.

3. 3. The circuit film according to claim 1, which satisfies the following condition 2: Condition 2: The stress retention rate after 10 minutes with the circuit film strained to 50% is 50% or more. The stress retention rate was calculated from the following formula, where F1 is the stress when the strain reaches 50% from the start of elongation, and F2 is the stress when the strain is maintained at 50% for 10 minutes. (Stress retention rate [%]) = (F2 / F1) x 100

4. 3. The circuit film according to claim 1, which satisfies the following condition 3: Condition 3: The loss tangent of the circuit film at 25° C. and a frequency of 1 Hz is 0.25 or less.

5. 3. The circuit film according to claim 1, which satisfies the following condition 4: Condition 4: The glass transition temperature of the circuit film is 0° C. or lower.

6. 3. The circuit film according to claim 1 or 2, which satisfies the following condition 5: Condition 5: The resin constituting the circuit film contains a segment of Chemical Formula 1. 【Chemistry 1】

7. The circuit film according to claim 6, which satisfies the following condition 6. Condition 6: The resin constituting the circuit film contains a segment of Chemical Formula 1 and a segment of Chemical Formula 2. 【Chemistry 2】

8. The film for circuits according to claim 7, which satisfies the following condition 7: Condition 7: The resin constituting the circuit film is a resin obtained by curing component A having a segment of chemical formula 1 and component B having segments of chemical formula 1 and chemical formula 2, and component A and component B are different components.

9. The circuit film according to claim 8, which satisfies the following condition 8. Condition 8: The resin constituting the circuit film is a resin obtained by curing a composition in which the mass ratio of component B to component A is 10% or more and 50% or less.

10. The film for circuits according to claim 9, which satisfies the following condition 9. Condition 9: The molecular weight of component B is 500 or less.

11. 3. An electric circuit comprising the circuit film according to claim 1 or 2 and a conductor circuit formed on the circuit film.

12. A healthcare sensor comprising the circuit film according to claim 1 or 2 and a conductor circuit formed on the circuit film.

13. A wearable sensor comprising the circuit film according to claim 1 or 2, and a conductor circuit formed on the circuit film.

Citation Information

Patent Citations

  • Active energy ray-curing resin composition, cured film and laminated body

    JP2010222568A

  • Polyurethane and method for producing polyurethane

    JP2015189886A

  • Composition for forming flexible resin, resin film, electric circuit body, and semiconductor device

    JP2018172460A

  • Curable resin composition for forming flexible resin and semiconductor device comprising the same

    JP2018203827A